Deep peroneal nerve paresis in a runner caused by ganglion at capitulum peronei - Dallari, D.; Pellacani, A.; Marinelli, A.; Verni, E.; Giunti, A. (The Journal of Sports Medicine and Physical Fitness, 2004)
Although lateral popliteal sciatic nerve damage is not one of the commonest diseases in the general population, it is quite frequent among athletes. Several physiopathologic mechanisms have been thought to bring about this damage in athletes. Soft tissue ganglions with neurological involvement of the lateral popliteal sciatic nerve or its terminal rami are in differential diagnosis with several lesions of this area, as direct or indirect trauma, subcutaneous rupture of anterior tibialis muscle and long peroneal muscle, disc hernia, intraspinal tumor, anterior tarsal tunnel syndrome, cysts, neurofibroma, baker's cyst, vascular claudication, stenosing or inflammatory pathology of 2(nd) motoneuron, antimicrobial agents for urinary tract infection (nitrofurnantoin). The authors report the case of a 34-year-old amateur athlete with a recent paralysis of the hallux extensor, paresis of the toe extensor and hyposthenia of the tibialis anterior. The patient had been suffering from episodes of lumbalgia for a long time. He was sent to us because neurological damage due to disc herniation was suspected. Electromyography, sonography, and CT showed peripheral compression of the deep peroneal nerve caused by a mucous cyst at the capitulum peronei, a ''rare'' condition. The patient underwent surgery to excise the cyst, which led to the rapid resolution of the nerve deficit shown by clinical and electromyographical tests. A meticulous anamnesis and accurate objective examination, followed by specific tests (radiographs, sonography, and possibly CT scan) generally enable a correct diagnosis to be made. If diagnosis and therapy are carried out correctly, and without delay, symptoms quickly resolve and the nerve deficit progressively regresses.